2014
DOI: 10.1093/ageing/afu170
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with grip strength decline in older adults

Abstract: Factors measured earlier in adulthood were associated with grip strength decline in late midlife and old adulthood. Gender-specific patterns of risk factors suggest that it may be worthwhile to conduct research on grip and muscle strength (and biological vitality) separately for men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
121
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(139 citation statements)
references
References 32 publications
12
121
5
1
Order By: Relevance
“…Decreased physical activity, malnourishment, chronic diseases, insulin resistance, chronic inflammation and imbalances in anabolic/ catabolic hormones have all been suggested as possible reasons for muscle wasting [14]. Moreover, some evidence suggests that men and women differ in terms of risk factors associated with the decline in grip strength in old age [15]. Our results point to physical activity as one of the main factors associated with greater muscle mass and strength in both sexes, corroborating most scientific evidence indicating the benefits of physical activity on muscle mass and function [16].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased physical activity, malnourishment, chronic diseases, insulin resistance, chronic inflammation and imbalances in anabolic/ catabolic hormones have all been suggested as possible reasons for muscle wasting [14]. Moreover, some evidence suggests that men and women differ in terms of risk factors associated with the decline in grip strength in old age [15]. Our results point to physical activity as one of the main factors associated with greater muscle mass and strength in both sexes, corroborating most scientific evidence indicating the benefits of physical activity on muscle mass and function [16].…”
Section: Discussionmentioning
confidence: 99%
“…Men were significantly stronger, but they also demonstrated steeper decline compared to women (Frederiksen et al 2006; Nahhas et al 2010; Sternang et al 2015a). Moreover, Nahhas et al (2010) found that the decline in grip strength begins in midlife and continues throughout life, which is consistent with another study suggesting accelerating declines in late life for men and women (Sternang et al 2015a). Moreover, as suggested in a phenotypic study of Swedish twins, grip strength trajectories might be affected by different environmental factors in men and women (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…Grip strength is a measure that captures early and recent exposures and depends on internal factors such as age and sex (Nahhas et al 2010; Rantanen et al 2000; Frederiksen et al 2006; Sternang et al 2015a). Men were significantly stronger, but they also demonstrated steeper decline compared to women (Frederiksen et al 2006; Nahhas et al 2010; Sternang et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors associated with a decline in grip strength seem to be more closely associated with lifestyle (e.g., smoking and stress) in women and with physical characteristics (e.g., mean arterial pressure, physical activity and chronic disorders) in men 4) . Based on 22-year follow-up data, Stenholm et al reported that long-term lifestyle factors, including physical activity, weight change, and smoking status, and physical health factors, including cardiovascular disease and diabetes, were strongly associated with a decline in grip strength in old age 53) .…”
Section: Determinant Factors Of Grip Strength: Life Course Approachmentioning
confidence: 97%
“…The literature has provided a wide age range reference value 1) and outlined aging patterns in relation to grip strength 2) . On the other hand, data have shown diverse age-related changes in grip strength 3) and associated factors 4) ; therefore, the "normal/true" aging process for grip strength over one's life-span, how much grip strength is needed in old age, and the determinant factors of grip strength remain as a challenge.…”
Section: Introductionmentioning
confidence: 99%